Blended Learning for Undergraduates in Nursing Profession: A Systematic Review of the Impact on Knowledge, Skills, Attitudes and Satisfaction - Awad ALI, Shaimaa Ahmed; ABED, Shaymaa Najm; Mohamed DIAB, Samar Salah Eldin (International Journal of Supply Chain Management, 2020)
Abstract In higher education, e-learning is gaining more and more impact, this new kind of traditional teaching and learning can be practiced in many ways. Several studies have compared face-to-face teaching to online learning and/or blended learning in order to try to define which of the formats provides, e.g., the highest learning outcome, creates the most satisfied students or has the highest rate of course completion. However, these studies often show that teaching and learning are influenced by more than teaching format alone. The review has a special interest in professional bachelor student’s education, and it focusses on the impact of e-learning on knowledge, skills, attitudes and satisfaction of students. The findings from the research papers included in the review show that students should have e-learning courses in Learning Management System. These courses will help them understand the aims of e-learning and the benefits of using it in developing their skills in learning.